2021
DOI: 10.1186/s12888-021-03469-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric emergency admissions during and after COVID-19 lockdown: short-term impact and long-term implications on mental health

Abstract: Background The ‘lockdown’ measures, adopted to restrict population movements in order to help curb the novel coronavirus disease 2019 (COVID-19) pandemic, contributed to a global mental health crisis. Although several studies have extensively examined the impact of lockdown measures on the psychological well-being of the general population, little is known about long-term implications. This study aimed to identify changes in psychiatric emergency department (ED) admissions between two 8-week pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
2
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 39 publications
5
60
2
7
Order By: Relevance
“…This discomfort could also account for the significantly higher number of admissions for psychomotor agitation and suicidal ideation/self-harm/suicide attempt, a trend already observed during the lockdown period by numerous studies [ 6 , 10 , 13 15 ], including our previous work, though it did not reach statistical significance [ 7 ]. Our results are in line with a Swiss study with a similar methodology [ 24 ] and support the hypothesis of long-term impact of the lockdown [ 4 , 16 ]. Nevertheless, these findings are contrasted by a French survey that documented a reduction in hospitalizations for self-harm in the same period [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…This discomfort could also account for the significantly higher number of admissions for psychomotor agitation and suicidal ideation/self-harm/suicide attempt, a trend already observed during the lockdown period by numerous studies [ 6 , 10 , 13 15 ], including our previous work, though it did not reach statistical significance [ 7 ]. Our results are in line with a Swiss study with a similar methodology [ 24 ] and support the hypothesis of long-term impact of the lockdown [ 4 , 16 ]. Nevertheless, these findings are contrasted by a French survey that documented a reduction in hospitalizations for self-harm in the same period [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been found in Northern England regarding primary care recorded self-harm, with a stronger decrease until August 2020 followed by a weaker decrease until May 2021 [ 9 ]. However, other locations have observed increasing trends during the first months of the pandemic [ 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social distancing measures, travel restrictions, and lockdowns/curfews were reimplemented. Despite the promising start of the vaccination campaign in December 2020, national surveys showed high levels of depression, anxiety, insomnia, and suicidal ideas in the general population in France [ 5 ] and some studies additionally suggested that postlockdown periods may be marked by more severe clinical conditions [ 6 ], raising the possibility of a delayed impact on self-harm rates. Clinicians particularly alerted in media of the situation in young people and an early study reported an increasing number of visits at an emergency room in Paris in people aged 15-year-old and below starting in September 2020 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the general population was more vulnerable to SI and SB development during later stages of the pandemic ( Balestrieri et al, 2021 , McIntyre et al, 2021 ). A possible explanation for this phenomenon may be the persistent and long-lasting impact of various psychosocial factors ( Zortea et al, 2020 ), including the evolution of the global economic crisis ( Sher, 2020b , Ambrosetti et al, 2021b , Costanza et al, 2021a , Pompili, 2021 ). Besides, the increase in suicide risk during the later stages of the pandemic might result from direct chronic biological consequences of the infection, including its hallmark pathology of hyperinflammation ( Sher, 2021 ), defined as the rapid proliferation of effector immune cell subsets and the excessive production of a multitude of pro-inflammatory cytokines by both immune and parenchymal cells.…”
Section: Introductionmentioning
confidence: 99%